Differential cross section measurements for the production of top quark pairs and of additional jets using dilepton events from pp collisions at s $$ \sqrt{s} $$ = 13 TeV - The CMS collaboration; A. Tumasyan; W. Adam; J. W. Andrejkovic; T. Bergauer; S. Chatterjee; K. Damanakis; M. Dragicevic; A. Escalante Del Valle; P. S. Hussain; M. Jeitler; N. Krammer; et al. (Journal of High Energy Physics, 2025)
Abstract Differential cross sections for top quark pair ( t t ¯ $$ t\overline{t} $$ ) production are measured in proton-proton collisions at a center-of-mass energy of 13 TeV using a sample of events containing two oppositely charged leptons. The data were recorded with the CMS detector at the CERN Large Hadron Collider and correspond to an integrated luminosity of 138 fb −1. The differential cross sections are measured as functions of kinematic observables of the t t ¯ $$ t\overline{t} $$ system, the top quark and antiquark and their decay products, as well as of the number of additional jets in the event. The results are presented as functions of up to three variables and are corrected to the parton and particle levels. When compared to standard model predictions based on quantum chromodynamics at different levels of accuracy, it is found that the calculations do not always describe the observed data. The deviations are found to be largest for the multi-differential cross sections.